Contract Interpretation: Brief Overview from the Standpoint of International and Trans-National Instruments - Карнаух, Богдан Петрович (Problems of legality, 2016)
The role of contract in modern social and economic order can hardly be overestimated. Contract constitutes the legal form of economic exchange and in the same time it is an instrument for self-regulation which is used by agents in the market. Therefore contract bears much resemblance to the state law. Just as the state law, contract provides some obligatory rules which must be followed. And just as the provisions of state law, the terms of a contract are put in words of natural language. Since natural language allows for much ambiguity and polysemy, the problem of finding out the exact meaning of contract terms constitutes an important issue of modern law of contracts. Contract interpretation is a traditional topic within the realm of contract law. That is why the issue is always in the spotlight of researchers’ attention. Amongst contemporary publications the works of Catherine Mitchell, Steve J Cornelius, Lord Justice Lewison and David Hughes address the issue. Paper objective. The main objective of the paper is to figure out the most modern tendencies relating to contract interpretation. This goal is achieved through the analysis of influential international and trans-national authorities such as Vienna Convention on Contracts for the International Sale of Goods (CISG), UNIDROIT Principles of International Commercial Contracts (PICC), Principles of European Contract Law (PECL), Draft Common Frame of Reference (DCFR), Common European Sales Law (CESL). First of all the paper provides a brief overview of two opposite approaches to the interpretation of contract, namely objective theory of interpretation and subjective theory of interpretation which are also known as reliance theory and theory of will. The author states pros and cons of each theory and then goes on to analyzing how those two theories are reconciled in PICC, PECL, DCFR, and CESL. Also the author pays attention to different factors which one has to take into account while interpreting the contract. In this context some brief comparative observations are made. The main trend in evolution of modern rules on contract interpretation is that the boundary dividing subjective and objective interpretation is being more and more erased. Those two approaches are now combined in one complex solution of the problem. This solution can be worded as a kind of rebuttable presumption according to which the contract must be construed from the standpoint of hypothetical reasonable persons put in the same factual situation as the parties, unless there are firm evidences that there was an actual mutual intention of the parties to attach the contract some different meaning (i.e. different from the meaning which can be inferred by using the first approach).